PENGEMBANGAN MEDIA GAME VISUAL NOVEL BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI ALJABAR - Sesar Guntur Jabali; Supriyono Supriyono; Puji Nugraheni (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
Education was strongly influenced by technological advances, moreover, teachers were required to be creative and innovative. One of them which can be applied for learning media was following existing technological developments. This study aims to produce learning media for ethnomathematics based visual novel games and to determine the validity, practicality and effectiveness to be suitably used by junior high school students. The development model used in this research was the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. This studied was involved 30 students and mathematics teacher at the analysis stage, three experts at the product validation stage and 10 students at the implementation stage. The resulted of the development research were in the form of ethnomathematics-based visual novel game media with a validity score of 86.7% (very valid criteria), a practicality score of 3.3 (good criteria), a score of 90% student learning completeness (complete) and a conceptual understanding of 83.7 % (very good criteria). From the resulted of the study it was concluded that the media was suitable to be used and increased students' conceptual understanding because it met the valid, practical and effective criteria.